(untitled) (INNOVATIVE ECONOMY, 2021)
Honak I.M. THEORETICAL SUBSTANTIATION OF THE DEFINITION OF CRYPTOCURRENCY AS MONEY Purpose. The aim of the article is elaboration of theoretical and practical aspects of definition and functioning of cryptocurrencies as money. Methodology of research. The following methods were used in the study: statistical analysis and comparison – in the study of problematic aspects of the definition of cryptocurrency as a kind of money; logical assessment – in substantiating the principles of determining cryptocurrency as a kind of money; generalization – in the process of formulating conclusions based on the results of the analysis. Findings. It is established that money is a financial asset with high liquidity, which can be quickly converted into paper money or coins, serve as an intermediary in money circulation (i.e. play the role of equivalent in exchange) and can be used for savings and therefore anything that can function as money, are money (including cryptocurrency coins). It is substantiated that cryptocurrency coins, as a type of money, perform the following functions: there is a potential to perform the function of a measure of value after reducing the significant volatility of the value of cryptocurrencies; partly as a medium of exchange due to high volatility, regulatory resistance and low prevalence, but prevalence will increase as traditional payment systems begin to integrate cryptocurrencies, cryptocurrencies have high convenience and inclusiveness, have the potential to reduce transaction costs, increase settlement speeds, develop cryptocurrency markets and increasing their prevalence; due to opposition from ESG investors and regulators, low confidence from a significant number of citizens (especially over the age of forty) and a significant speculative component of cryptocurrency coins, only partially serve as a means of accumulation, however, the demand for cryptocurrencies from investors is constantly growing. Originality. The definition of cryptocurrency (cryptocurrency coin, cryptocoin) as a new digital type of money, which can measure the value of goods, services and other currencies, used for circulation, savings and investment, protected by cryptographic code with the inability to counterfeit or copy, and issue which everyone has the opportunity with the Internet and the necessary equipment with complete anonymity of the issuer (miner). Practical value. The main results of the conducted study will create favourable conditions for a better understanding of cryptocurrency as a new type of money, which will allow them to be more widely used in the economic activities of businesses and countries. Key words: money, cryptocurrency, cryptocoin, cryptocurrency coin, mining, cryptocurrency functions, Ethereum, Monero, monetary aggregate.